Differential effects of growth restriction and immaturity on predicted psychomotor development at 4 years of age in preterm infantsAJOG Global Reports at a Glance - Arne Jensen, MD; Niels Rochow, MD, PhD; Manfred Voigt, PhD; Gerhard Neuhäuser, MD (Elsevier, 2024)
BACKGROUND: Fetal growth restriction and immaturity are associated with poor neurocognitive development and child psychopathology affecting educational success at school and beyond. However, the differential effects of either obstetrical risk factor on predicted psychomotor development have not yet been deciphered. OBJECTIVE: This study aimed to separately study the impact of growth restriction and that of immaturity on predicted psychomotor development at the preschool age of 4.3 (standard deviation, 0.8) years using birthweight percentiles in a prospective cohort of preterm infants born at ≤37+6/7 weeks of gestation. Differences between small for gestational age newborns with intrauterine growth restriction and those without were described. We examined predicted total psychomotor development score, predicted developmental disability index, calculated morphometric vitality index, and predicted intelligence quotient, Porteus Maze test score, and neurologic examination optimality score in 854 preterm infants from a large prospective screening cohort (cranial ultrasound screening, n=5,301). STUDY DESIGN: This was a prospective cranial ultrasound screening study with a single-center cohort observational design (data collection done from 1984-1988, analysis done in 2022). The study included 5,301 live-born infants, of whom 854 (16.1%) were preterm infants (≤37+6/7 weeks' gestation), and was conducted on the day of discharge of the mother at 5 to 8 days postpartum from a level 3 perinatal center. Predicted psychomotor development, as assessed by the predicted total psychomotor development score, predicted developmental disability index, calculated morphometric vitality index, predicted intelligence quotient, Porteus Maze test score, and neurologic examination optimality score were calculated. We related psychomotor development indices and measures to gestational age in 3 groups of birthweight percentiles (ie, 10%, 50%, and 90% for small, appropriate, and large for gestational age newborns, respectively) using linear regression analysis, analysis of variance, multivariate analysis of variance, and t test procedures. RESULTS: The key result of our study is the observation that in preterm infants born at ≤37+6/7 weeks of gestation, growth restriction as compared with immaturity is the prime risk factor for impairment of overall predicted psychomotor development, intelligence quotient, Porteus Maze test results, and neurologic examination optimality score at the preschool age of 4.3 (standard deviation, 0.8) years (P<.001). This is particularly true for intrauterine growth restriction. These detrimental effects of growth restriction become more prominent with decreasing gestational age (P<.001). As expected, growth restriction in preterm infants born at ≤37+6/7 weeks of gestation was associated with a number of obstetrical risk factors, including hypertension in pregnancy (P<.001), multiple pregnancy (P<.001), pathologic cardiotocography (P=.001), and low pH (P=.007), increased pCO2 (P=.009), and poor pO2 (P<.001) in umbilical arterial blood. Of note, there were no differences in cerebral hemorrhage or white matter damage among small, appropriate, and large for gestational age birthweight percentile groups, suggesting an independent mechanism of brain injury caused by preterm growth restriction resulting in poor psychomotor development. CONCLUSION: Compared with immaturity, growth restriction in preterm infants has more intense detrimental effects on psychomotor development, necessitating improved risk stratification. This finding has implications for clinical management, parental consultation, and early intervention strategies to improve school performance, educational success, and mental health in children. The mechanisms of brain injury specific to growth restriction in preterm infants require further elucidation.